The migration of Ascaris suum larvae, and the associated pulmonary inflammatory response in susceptible C57BL/6j and resistant CBA/Ca mice - Lewis, R.; Behnke, Jerzy M.; Cassidy, J.P.; Stafford, P.; Murray, N.; Holland, Celia V. (Cambridge University Press, 2007)
Ascariasis is an important infection in humans (Ascaris lumbricoides) and pigs (Ascaris suum) and individuals appear to be predisposed to either heavy or light worm burdens. These extremes of susceptibility and resistance are represented in a mouse model by 2 strains of mice, CBA mice showing high resistance to infection and C57BL/6 which are highly susceptible, as reflected in worm burdens in the lungs 6–7 days after infection. In an attempt to identify the point at which the difference between these 2 strains is first manifested, we quantified worm burdens at key stages during infection leading up to the pulmonary stage of development. Thus mice were inoculated with fully embryonated A. suum eggs and larval burdens were enumerated in the large intestine and rectum, liver and lungs of the 2 strains at 6 h post-inoculation (p.i.) and on each of days 1–8 p.i. inclusively. A higher percentage of the total inoculum was recovered from the intestine/rectum of C57BL/6j mice in contrast to CBA/Ca mice at 6 h p.i. Larvae were recovered from the intestinal contents and also whilst actively migrating through the large intestinal wall. The number of larvae recovered was significantly reduced in CBA/Ca mice in contrast to C57BL/6j mice between the phase of migration from the liver and arrival in the lungs. The combined results of the inoculation of mice with corticosteroids and the examination of the change in profile and number of leukocytes present in bronchoalveolar lavage fluid suggested that the pulmonary inflammatory immune response was not prominently involved in primary protection of mice to A. suum infection in the latter days of infection in the lungs. The susceptible C57BL/6j mice produced a BAL response almost twice as intense as that of resistant CBA/Ca mice with stronger neutrophil, lymphocyte and eosinophil but not macrophage components, suggesting that the difference in worm burdens between the strains was generated earlier in the course of infection. These results were further corroborated by a histological examination of the lung tissues which showed that the passage of the larval stages of A. suum through the mouse lungs was associated with a marked inflammatory response in both strains. Again, C57BL/6j mice exhibited increased inflammation relative to CBA/Ca mice. Hence some hepatic/post-hepatic factor that varies between the 2 strains, but exerts its effect before the lung phase plays a critical role in determining the success of larvae through the host tissues. The possible sites of this host defence are reviewed.